Food tolerance and quality of eating after bariatric surgery: an observational study of a German Obesity Center - Jungert, Alexandra; Finze, Alida; Betzler, Alexander; Reißfelder, Christoph; Blank, Susanne; Otto, Mirko; Vassilev, Georgi; Betzler, Johanna (Journal of Clinical Medicine, 2025)
Background: Bariatric surgeries, specifically laparoscopic sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB), are a common intervention for morbid obesity, significantly affecting food tolerance and quality of eating. Understanding these changes is crucial for improving postoperative care and long-term success. Methods: This observational study at University Hospital Mannheim involved 91 patients, aged between 18 and 65 year, who underwent SG or RYGB between 2009 and 2019. Food tolerance was assessed between 25 days and 117 months after surgery using the validated score by Suter et al. (Food Tolerance Score, FTS) and an additional score evaluating tolerance to specific food groups and quality of life. Data on body composition were collected through Bioelectrical Impedance Analysis (BIA) at follow-up visits. Statistical analyses included linear mixed models to analyze the association of food tolerance with body composition changes. Results: The FTS indicated moderate or poor food tolerance in 62.6% of patients, with no significant differences between SG and RYGB. Considering the results of the additional score, food groups such as red meat, wheat products, raw vegetables, carbon dioxide, fatty foods, convenience food, and sweets were the most poorly tolerated food groups. A total of 57 of the participants had a baseline and follow-up BIA measurement. Postoperatively, a significant reduction in body weight and BMI as well as in BIA parameters (fat mass, lean mass, body cell mass, and phase angle) was found. Quality of life improved after bariatric surgery and 76.9% rated their nutritional status as good or excellent, despite possible food intolerances. Conclusions: Bariatric surgery significantly reduces weight and alters food tolerance. Despite moderate or poor food tolerance, patients reported high satisfaction with their nutritional status and quality of life. Detailed food tolerance assessments and personalized dietary follow-ups are essential for the early detection and management of postoperative malnutrition, ensuring sustained weight loss and improved health outcomes.
Gesehen am 04.09.2025